Caracterização arqueométrica de pinturas rupestres pré-históricas, pigmentos minerais naturais e eflorescências salinas de sítios arqueológicos - Luis Carlos Duarte Cavalcante (2012)
The present experimental work was devoted to the chemical and mineralogical characterization of prehistoric rock paintings, of mineral pigments and of saline efflorescences from archaeological sites located in the states of Piauí, Bahia and Ceará, in Brazil, and in the Perito Moreno National Park, in Argentina. Samples were investigated in the laboratory by several analytical techniques, including (i) 57Fe transmission and conversion electron Mössbauer spectroscopy; (ii) grazing incidence X-ray diffraction; (iii) energy dispersive spectroscopy; (iv) scanning electronic microscopy; (v) powder X-ray diffraction; (vi) energy dispersive X-ray fluorescence and (vii) Fourier-transform infrared spectroscopy.Results revelated that the red paintings were basically prepared with hematite (Fe2O3)-rich materials; the yellow paintings contained goethite (FeOOH); the black paintings were essentially composed by carbon, presumably from charcoal (except the sample PCI-03, whichwas found to contain carbon together with hematite), and the gray painting was prepared with a mixture of carbon and aluminosilicate minerals. The iron oxides and oxyhydroxides appearas being of small particle sizes, high isomorphic substituition of different cations for iron and low crystallinity. Results related to saline efflorescence samples revealed the occurrence ofchabazite (Ca2Al4Si8O24.12H2O); partheite (Ca2Al4Si4O15(OH)2.4H2O); taranakite (H6K3Al5(PO4)8.18H2O); newberyite (MgHPO4.3H2O); kaolinite (Al2Si2O5(OH)4); brushite (CaPO3(OH).2H2O); gypsum (CaSO4.2H2O); KAl3(SO4)2(OH)6; potassium aluminum sulfate (KAl(SO4)2); K2SO4.7KHSO4.H2O and 5ZnO.Al2O3.ZnSO4.15H2O. The red pigments contained predominantly hematite, together with quartz, kaolinite, illite and KAl3(SO4)2(OH)6, whereas the yellow pigment contained goethite, quartz and kaolinite. Thewhite pigment was composed mainly by illite and quartz.